Speech Act of Advice and Its Social Variables as Acquired by Senior Students of English Department of Andalas University in 2019 - Gyunia Jenetto; Hanafi Hanafi (Vivid: Journal of Language and Literature, 2019)
This research analyzes the form of the speech act of advice acquired by senior students at English Department of Andalas University in 2019. The identified structures of advice were then described about politeness strategy being used and the social factors (Power, Social Distance, and Rate of Imposition) that underlie the selection of the form and strategies. Data were gathered using online DCT that made use of Google Form platform. As many as 32 senior students of the department in 2019 participated in this research and filled in their responses completely to the 12 situations presented in the online DCT. The situations were designed as similar as possible to Indonesian students' daily life situations in West Sumatera and written in Indonesian. However, the responses were required in English. The results of the analyses revealed that most participants tended to use hedging type of advice (57%) with a positive politeness strategy (76%). In addition, social variables such as social distance appeared to play a significant role in the participants' selection of the politeness form and strategy. When the social distance was close between an advisor and an advisee, the advisor tended to switch to the direct mode form and direct politeness strategy. However, when an advisor assumed a far social distance against the listener, s/he tended to advise the listener in a more indirect form and strategy regardless of the listener's power status.